Low-cost prototyping of nitinol wires/frames using polymeric cores and sacrificial fixtures with application in individualized frames anchoring through the atrial septum - Hemanta Dulal; Trey Swan; Subhi J. Al’Aref; Seyedhamidreza Alaie (Scientific Reports, 2023)
Abstract Self-expanding frames for minimally invasive implants are typically made from nitinol wires and are heat treated to maintain the desired shapes. In the process of heat treatment, nitinol structures are placed in a high-temperature oven, while they are confined by a fixture. During this process, nitinol exerts a high amount of force. Accordingly, a fixture requires high mechanical strength and temperature resistance; this is why fixtures are typically made from metals. The use of metal fixture also increases the turnaround time and cost. However, accelerating this process is beneficial in many applications, such as rapid development of medical implants that are patient-specific. Inspired by the use of sacrificial layers in microfabrication technology, here we propose a novel method for shape setting nitinol wires using a sacrificial metal fixture. In this process, the nitinol wires are first aligned inside copper hypotubes. Next, the forming process is done using hand-held tools to shape complex geometrical structures, annealing the nitinol reinforced by copper, and then selectively etching copper hypotubes in ammonium persulfate solutions. In this process, other sacrificial cores, which are 3D printed or cast from low-cost polymers, are also used. This combination of polymeric cores and minimal use of metals enables reducing the cost and the turnaround time. As a proof of concept, we showed that this process was capable of fabricating springs with mm or sub-mm diameters. The result showed a change of less than 5% in the intended diameter of the nitinol spring with diameters ranging from ~ 0.7 to 1.9 mm, which confirms copper as a suitable sacrificial fixture to obtain the desired complex geometry for nitinol. A metric, based on the elastic strain stored in copper is suggested to predict the possible variation of the intended dimensions in this process. Finally, to demonstrate the potential of this method, as proof of concept, we fabricated NiTi wire frames designed for anchoring through the atrial septum. These frames demonstrated septal defect occluders that were designed based on a patient’s cardiac image available in the public domain. This low-cost rapid fabrication technique is highly beneficial for a variety of applications in engineering and medicine with specific applications in rapid prototyping of medical implants.